2020
DOI: 10.3390/f11090978
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of BplERD15 Enhances Drought Tolerance in Betula platyphylla Suk.

Abstract: In this study, we report the cloning and functional characterization of an early responsive gene, BplERD15, from Betula platyphylla Suk to dehydration. BplERD15 is located in the same branch as Morus indica Linnaeus ERD15 and Arabidopsis Heynh ERD15 in the phylogenetic tree built with ERD family protein sequences. The tissue-specific expression patterns of BplERD15 were characterized using qRT-PCR and the results showed that the transcript levels of BplERD15 in six tissues were ranked from the highest to the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Under drought stress, plants will produce a series of protective mechanisms to maintain survival, such as changing root and leaf morphology [6] [7] , changing metabolites [8] , regulating drought resistance gene expression [9] . In broad-leaved tree species and crops, the research on response to drought stress is relatively su cient, such as birch [10] , poplar [11] , soybean [12] , corn [13] , etc.However, few relevant studies involve larch. So it is necessary to study the drought resistance mechanism of hybrid larch.…”
Section: Main Textmentioning
confidence: 99%
“…Under drought stress, plants will produce a series of protective mechanisms to maintain survival, such as changing root and leaf morphology [6] [7] , changing metabolites [8] , regulating drought resistance gene expression [9] . In broad-leaved tree species and crops, the research on response to drought stress is relatively su cient, such as birch [10] , poplar [11] , soybean [12] , corn [13] , etc.However, few relevant studies involve larch. So it is necessary to study the drought resistance mechanism of hybrid larch.…”
Section: Main Textmentioning
confidence: 99%
“…To measure the physiological changes, the plants under drought treatment for seven days were harvested for measuring the activities of SOD and POD, the contents of H 2 O 2 , superoxide radicals (O 2 − ), MDA and electrolyte leakage (EL). MDA, SOD and POD were measured following the methods as described previously (Wang et al, 2010), while EL was measured as described in our early publication (Lv et al, 2020b). H 2 O 2 and O 2 − were measured using the kit (Hydrogen peroxide content kit, H2O2-2-Y, Superoxide anion kit, SA-2-G, Suzhou Comin Biotechnology).…”
Section: Drought Stress Treatmentmentioning
confidence: 99%
“…It was assumed that the BpUVR8 enhances the susceptibility to ABA, demonstrating ABA regulates BpUVR8 and can inhibit the germination of seed ). The early response to dehydration 15 gene (BplERD15) expression that was induced by drought, salt, and osmotic stress, was also inhibited under ABA treatment in B. platyphylla transgenic lines (Lv et al 2020b).…”
Section: Phytohormones Response Of Betula Platyphylla To Abiotic Stressmentioning
confidence: 99%
“…Li et al (2020a) found that BpARF1 RNAi lines reduce the EL and water loss, while BpARF1 OE lines showed the opposite physiological changes under drought stress. Meanwhile, the BplERD15 OE line showed a lower EL rate under drought stress, suggesting that BplERD15 is an abiotic stress-responsive gene that can reduce cell death under drought stress conditions (Lv et al 2020b). Under cold stress, Lv et al (2019) revealed that BpERF13 OE lines showed a higher EL rate compared to WT plants under cold stress.…”
Section: Electrolyte Leakagementioning
confidence: 99%